Artikel 48 der Weimarer Verfassung: Hugo Preuß und Carl Schmitt im Streit über den „Diktaturartikel“ - Yasuhiro Endo (Právněhistorické studie)
The abuse of Article 48 of the Weimar Constitution during the late presidency of Hindenburg has been criticized in many previous studies as one of the key factors of the collapse of the Weimar Republic that led to the establishment of the Third Reich, resulting from the lack of understanding of the parliamentary democracy. Whereas those criticisms have arisen primarily from the analysis of the consequences, this paper analyzes the issue of the executed presidential emergency powers with an integrative approach by comparing the arguments by Preuß, the drafter of Article 48, and Schmitt, taking into account the perspectives of members of the constitutional assembly as well as their contemporaneous intellectuals. While Preuß and Schmitt may appear generally contrastive in their beliefs and theories, some implicit logical agreements are observed, such as those on their interpretations of the relation between the first and the second sentences in Article 48, paragraph 2, and their thoughts regarding the handling of the law of the Reich that should be in Article 48, paragraph 5. With the findings of their commonalities and others in their theories, this paper attempts to contribute to refining the current systems of law and democracy for emergency situations in various contexts.